Strategies for Islamic Religious Education Teachers Difficulties in Learning the Qur'an in Students at SMP Negeri 24 Medan - Khairun Nisa Bunaiya (Al-Ulum: Jurnal Pendidikan Islam, 2023)
The aims of this study were to find out: 1) how PAI teachers overcome obstacles and difficulties in reading the Qur'an through the use of the habituation method; 2) the inhibiting factors and what is the solution. This research uses a qualitative approach in the form of a case study. Data collection was carried out by means of observation and interviews. Respondents are students of SMP Negeri 24 Medan. The results of the research reveal that the difficulty in reading the Qur'an can be increased through the use of the habituation method.